Centrex or PBX : the impact of IP - Abrahams, John R. (Artech House telecommunications library., 2003)
Annotation The current trend for business telecommunications is to Internet protocol telephony, which integrates voice, video and data traffic. This new book offers guidance to those who have the responsibility to manage, design, and upgrade data networks to carry IP telephony. The book describes the IP-Centrex option of having the telephone company take responsibility for the service delivery.